Analisis Tarif Angkutan Umum Jurusan Palangka Raya – Pontianak - Maretina Eka Sinta (Media Ilmiah Teknik Sipil, 2017)
West Kalimantan, especially Pontianak, currently emphasizes the field of land transportation. Road construction gets the highest priority. This is done considering there are still many regions remote that have not been reached by the existing road network. With the existence of the land route then the current goods and people will be more and more, this opens up opportunities for public transport services that serve the route from Palangka Raya to Pontianak. This research was conducted by field survey, data collection divided into two, primary and secondary data. This study aims to determine the cost public transport vehicle operations in the direction of Palangka Raya to Pontianak and to find out the rates ideal public transport passengers majoring in Palangka Raya Pontianak in accordance with the operational costs issued. The general freight rates for the Palangka Raya - Pontianak major that apply at the time of the study now is Rp. 900,000.00 org/rit. With a general tariff of Rp. 900,000.00 org/rit, and basic tariff of Rp. 464,298,56org/rit then provide benefits for transport entrepreneurs amounting to Rp. 435,701.44 rit/org or around 49%. So as to provide decent benefits for the public transport manager in the Palangka department Raya - Pontianak.